Towards Inclusive Green Growth in Africa: Critical energy efficiency synergies and governance thresholds - Isaac K. Ofori; Emmanuel Gbolonyo; Nathanael Ojong (Journal of Cleaner Production, 2022)
This study contributes to the scholarly literature on the achievement of sustainable development in light of the UN's Agenda 2030 and African Union's Agenda 2063 by examining pathways through which energy efficiency (EE) promotes inclusive green growth (IGG) in Africa. Our contribution is novel from both the conceptual and empirical perspectives. With regard to the former, we develop a framework on how EE and governance feed into IGG, and on the latter, our contribution is based on country-level data for 23 African countries for the period 1996 – 2020. First, evidence from generalised method of moments (GMM) estimator shows that EE is not unconditionally effective for spurring IGG. Second, we find that governance is both directly, and indirectly effective for repackaging EE to foster IGG. In particular, the evidence suggests that governance mechanisms for controlling corruption while ensuring regulatory quality and government effectiveness are keys for forming relevant synergies with EE to foster IGG. Third, regarding the socioeconomic sustainability (SES) and environmental sustainability (EVS) dichotomy of IGG, we find that compared to the former, the EE-governance pathway is more effective for driving the latter. We also make some policy recommendations.
Keywords: I3; O11; O43; O44; O55; Q01; Q43; Q56; 330; Africa; Inclusive Growth; Greenhouse Gases; Environmental Sustainability; Carbon Intensity; Sustainable Development